EFFECT OF BORON CONTENT ON THE MICROSTRUCTURE AND PROPERTIES OF IRON–BORON–CARBON ALLOYS DURING THE HARDENING PROCESS - Erkinjonov Abdulkhamid Bakhtiyorjon ugli; Yulchieva Surayyo Bakhramovna; Turakhodjaev Nodir Djakhongirovich (Modern American Journals, 2025)
This article investigates the influence of boron (B) on the microstructure and mechanical properties of steel. The results demonstrate that the addition of small amounts of boron significantly enhances the hardenability of steel, surpassing traditional alloying elements such as chromium (Cr), molybdenum (Mo), and tungsten (W). Even under relatively slow cooling conditions such as air quenching, a fully martensitic structure can be achieved due to boron's effect. Microstructural analyses using optical microscopy (OM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) confirmed the formation of primary and secondary boron carbides, such as M2(B, C), M23(C, B)6, and M7(C, B)3 phases. These carbides were predominantly distributed around martensitic areas, indicating boron’s tendency to segregate at high defect density regions. Furthermore, the study found that increasing boron content enhances microhardness up to a certain level, after which the effect diminishes. The findings contribute to the development of wear-resistant, high-strength steels suitable for energy-efficient and cost-effective industrial applications.
Keywords: Boron; steel; hardenability; microstructure; martensite; boron carbides; phase transformation; mechanical properties.